Revisiting limits to legal mobilization for global climate justice - Brandon Barclay Derman (Oñati Socio-Legal Series)
Amidst disproportionate climate-related harms and inadequate responses, affected groups have turned to legal mobilization. This paper analyzes socio-ecological complexity and territorial limits as themes of enduring relevance in official responses to the Inuit Circumpolar Council’s and Maldives’ foundational legal claims that climate change violates human rights, considering these against the backdrop of evolving understanding of responsibility for climate-related harm in scientific, political, and public discourse. The claims demonstrated that when legal analysis integrates scientific and traditional knowledge, climate change can be seen as violating rights internationally, and identifiable actors as culpable. Respondents disagreed, citing the complexity of climate-related harm, which combines multiple human actors, environmental processes, probability, prediction, and extraterritorial impact. Unresolved gaps between these interpretations raise doubts about law’s relevance to growing global inequities of climate change and other processes that mix people, places, and things.